Manufacture and study of new polystyrene scintillators - Senchishin, V.G.; Vasilchuk, V.L.; Borisenko, A.Yu.; Lebedev, V.N.; Adadurov, A.F.; Khlapova, N.P.; Titskaja, V.D.; Koba, V.S.; Pelipyagina, L.E.; Miroshnichenko, L.A.; Leman, V.E.; Osadchenko, V.N.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The main optical characteristics and radiation hardness of new polystyrene scintillator UPS98GC were studied. The scintillator UPS-98GC was compared to SCSN-81, produced by Kuraray Co. which is often used in high-energy physics experiments. The dependence of scintillator properties on radiation dose rates as well as on total dose values was studied. It is shown that for relatively small dose rates closed to those expected during scintillator lifetime, our UPS98GC does not yield to SCSN-81.